Assessing the Feasibility of Implementing Budget Amendment Powers of the Gauteng Provincial Legislature - Moraka, Mmusi Andrew (University of the Witwatersrand, Johannesburg, 2021)
This study investigates the feasibility of implementing the budget amendment powers of the GPL as provided for in the Gauteng Money Bills Amendment Procedures and Related Matters Act of 2019. The study employs a qualitative case study approach using the theoretical lens of the new institutionalism school of thought to examine the political and institutional arrangements at the GPL that may facilitate or constrain the implementation of the budget amendment powers. The introduction of legislative powers to amend money bills in South Africa follows on the growing international trend sponsored by the World Bank, International Monetary Fund (IMF) and international donors to strengthen legislative scrutiny of public finances as a way of improving governance and enhancing accountability in developing countries. It also comes at the time when the South African legislative sector is facing sharp public scrutiny about the efficacy of its oversight mechanisms in the wake of media reports and Auditor General’s reports that are pointing out what seems to be relentless acts of maladministration, irregular and fruitless expenditure as well as corruption in the public sector
A research report submitted to the Faculty of Commerce, Law and Management, University of Witwatersrand, in partial fulfillment of the requirements for the Master of Management Degree in the field of Public Sector Monitoring and Evaluation, Johannesburg 2021
Keywords: budget amendment powers; Gauteng Money Bills Amendment Procedures; Related Matters Act of 2019; South Africa; UCTD; SDG-8: Decent work and economic growth